2011
DOI: 10.5209/rev_sjop.2011.v14.n2.43
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Update of the Social Anxiety Screening Scale (SASS/EDAS) in a Spanish Adolescent Population

Abstract: The aim of this work was to update the validation of the Social Anxiety Screening Scale (SASS/EDAS) in a sample of Spanish adolescents. To achieve this, one study with a sample of 1489 students in secondary education, of ages 14 to 17 years, were carried out. The psychometric properties of EDAS were examined through confirmatory factor analysis, reliability (Cronbach's alpha), temporal stability (test-retest), and concurrent criterion validity. The results supported the three-independent-factor structure (avoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 36 publications
(51 reference statements)
3
4
0
Order By: Relevance
“…These results indicate alpha coefficients above the recommended value of .70 by Nunnally (1978) or .60 for reliable self-report instruments (Holmbeck et al, 2008). In addition, they are consistent with prior studies, showing values between .80 and .89 for EDAS scales (Olivares et al, 2004;Piqueras, Olivares, Hidalgo et al, 2011;Piqueras, Olivares, Vera-Villarroel et al, 2012;Vera-Villarroel et al, 2007). They are also comparable to those reported for other well-established self-reports that assess adolescent SAD (for example: SPAI, SPAI-B, SPAI-C, LSAS-CA, SPIN, SAS-A, etc.).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…These results indicate alpha coefficients above the recommended value of .70 by Nunnally (1978) or .60 for reliable self-report instruments (Holmbeck et al, 2008). In addition, they are consistent with prior studies, showing values between .80 and .89 for EDAS scales (Olivares et al, 2004;Piqueras, Olivares, Hidalgo et al, 2011;Piqueras, Olivares, Vera-Villarroel et al, 2012;Vera-Villarroel et al, 2007). They are also comparable to those reported for other well-established self-reports that assess adolescent SAD (for example: SPAI, SPAI-B, SPAI-C, LSAS-CA, SPIN, SAS-A, etc.).…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have shown that this measure has a three-factor structure: Avoidance, Distress and Interference (Piqueras, Olivares, Hidalgo, Vera-Villarroel, & Marzo, 2011;Piqueras, Olivares, Vera-Villarroel, Marzo, & Kuhne, 2012;Vera-Villarroel, et al, 2007). All these studies have indicated that the alpha values of internal consistency of the three subscales are above .76; the scores are temporally reliable (.48-.60) and are associated significantly with other wellestablished measures, such as the SPAI and the SAS-A, with values between .50 and .76 (Olivares et al, 2004;Piqueras, Olivares, Hidalgo et al, 2011; SOCIAL ANXIETY SCREENING Piqueras, Olivares, Vera-Villarroel et al, 2012;Vera-Villarroel et al, 2007).…”
Section: Screening Utility Of the Social Anxiety Screeningmentioning
confidence: 99%
See 2 more Smart Citations
“…This measure consists of 10 items: 2 are dichotomous and the remaining 8 have threeindependent-factor structure (avoidance, distress, and interference). Validation of the scale is limited to Hispanic populations Olivares et al 2004b ;Piqueras et al 2011Piqueras et al , 2012bVera-Villarroel et al 2007 ).…”
Section: Scales Designed or Adapted To Measure Social Anxiety In Adolmentioning
confidence: 99%